2012
DOI: 10.1002/bip.22032
|View full text |Cite
|
Sign up to set email alerts
|

N‐ and c‐terminal extensions of μ‐conotoxins increase potency and selectivity for neuronal sodium channels

Abstract: μ-Conotoxins are peptide blockers of voltage-gated sodium channels (sodium channels), inhibiting tetrodotoxin-sensitive neuronal (Na(v) 1.2) and skeletal (Na(v) 1.4) subtypes with highest affinity. Structure-activity relationship studies of μ-conotoxins SIIIA, TIIIA, and KIIIA have shown that it is mainly the C-terminal part of the three-loop peptide that is involved in binding to the sodium channel. In this study, we characterize the effect of N- and C-terminal extensions of μ-conotoxins SIIIA, SIIIB, and TII… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…To improve the potency of Pn, we designed a first series of mutants (Series 1) using data available from structurefunction studies on KIIIA and other m-conotoxins ( Fig. 1D) (19,20,(32)(33)(34)(35)(36). From this first series of mutants, PnM2 showed the most promising increase in activity when tested on Na V 1.2-Na V 1.6 ( Table 2).…”
Section: Electrophysiological Characterization Of Pn and Mutantsmentioning
confidence: 99%
“…To improve the potency of Pn, we designed a first series of mutants (Series 1) using data available from structurefunction studies on KIIIA and other m-conotoxins ( Fig. 1D) (19,20,(32)(33)(34)(35)(36). From this first series of mutants, PnM2 showed the most promising increase in activity when tested on Na V 1.2-Na V 1.6 ( Table 2).…”
Section: Electrophysiological Characterization Of Pn and Mutantsmentioning
confidence: 99%
“…It was suggested that the negative charge at this position created an unfavorable interaction with the binding site within the sodium channel [66]. More recent work has shown that addition of either a neutral residue (μ-TIIIA[E15A, 23A]) or basic residue (μ-TIIIA[E15A, 23K]) to the C-terminus decreased overall potency for all subtypes, but increased preference for Na V 1.2 [67]. Based on these findings, further positional scanning of Glu15 would be of interest to explore whether the selectivity profiles of μ-TIIIA could be shifted in favor of pain-relevant Na V 1-subtypes.…”
Section: Muscle-subtype Preferring μ-Conotoxinsmentioning
confidence: 99%
“…These data were interesting in light of functional data which suggested that the N-terminus was important for subtype selectivity, while the C-terminus contributed mainly to neuronal subtype interactions [78]. Schroeder et al explored the structural and functional consequences of N-terminal modification of μ-SIIIA/B [67]. Replacement of the N-terminal pyroglutamate (Pyr1 or single letter code Z) with charged residues (i.e., μ-SIIIA[Z1R] and μ-SIIIB[Z1E]) either decreased (μ-SIIIA) or increased (μ-SIIIB) preference for Na V 1.2.…”
Section: Neuronal-subtype Preferring μ-Conotoxinsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast with these two studies, adding residues to the N-terminus of SIIIA, SIIIB and TIIIA has been shown to change their selectivity preference from rat muscle channels to rat neuronal VGSCs [121]. This suggests that N-terminal residues also contribute to the toxins’ affinity and selectivity.…”
Section: Conotoxinsmentioning
confidence: 99%